Association Between Weight-Adjusted Waist Circumference Index and Metabolic Disease-Associated Fatty Liver Disease: A Retrospective Study - Tang T; Fan H; Yu Q; Rao X; Shi Y; Tong X; Feng L; Xu Z; Fu X; Chen J; Zhang X; Tang J; et al. (Risk Management and Healthcare Policy)
Ting Tang,1,* Hua Fan,2,* Qingwen Yu,1 Xiyun Rao,1 Yongmin Shi,1 Xuhan Tong,1 Lanlan Feng,1 Zhao Xu,1 Xinyan Fu,1 Juan Chen,1 Xingwei Zhang,1 Jiake Tang,1 Hu Wang,1 Mingwei Wang1,3– 6 1Department of Cardiology, the Affiliated Hospital of Hangzhou Normal University, Hangzhou Normal University, Hangzhou, Zhejiang, 310015, People’s Republic of China; 2School of Clinical Medicine, The First Affiliated Hospital of Henan University of Science and Technology, Luoyang, Henan, 471003, People’s Republic of China; 3Zhejiang Key Laboratory of Medical Epigenetics, Hangzhou Normal University, Hangzhou, Zhejiang, 310015, People’s Republic of China; 4Engineering Research Center of Mobile Health Management System&Ministry of Education, Hangzhou Normal University, Hangzhou, Zhejiang, 310015, People’s Republic of China; 5Department of Cardiology, Hangzhou Lin’an Fourth People’s Hospital, Hangzhou, Zhejiang, 311321, People’s Republic of China; 6Department of Cardiology, Jiande First People’s Hospital, Hangzhou, Zhejiang, 311600, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hu Wang, Email wanghu19860315@163.com Mingwei Wang, Email wmw990556@hznu.edu.cnBackground: Metabolic disease-associated fatty liver disease has brought significant challenges to public health and social-economics. There is a need for a straightforward and effective method to screen for metabolic disease-associated fatty liver disease. The weight-adjusted waist circumference index offers a comprehensive reflection of visceral fat accumulation and skeletal muscle loss. This study aims to explore the relationship between weight-adjusted waist circumference index and hepatic steatosis and hepatic fibrosis.Methods: This single-centered study screened 288 participants from the outpatient department of the Affiliated Hospital of Hangzhou Normal University (Hangzhou, China). Multiple linear regression models were utilized to assess the association between weight-adjusted waist circumference index and hepatic steatosis and hepatic fibrosis. The subgroup analysis was carried out according to sex, smoking, drinking, BMI, cardiovascular disease, diabetes and hypertension.Results: Metabolic disease-associated fatty liver disease was diagnosed in 185 out of 288 patients. Multivariate linear regression analysis indicated a positive linear correlation between weight-adjusted waist circumference index and hepatic steatosis and hepatic fibrosis (P < 0.05). Analysis of subgroups revealed a stronger positive correlation between weight-adjusted waist circumference index and controlled attenuation parameter among participants aged 18– 59 years and smokers (P < 0.05). Positive correlations between weight-adjusted waist circumference index and hepatic fibrosis were observed in participants who were alcohol consumers, male, had a body mass index of > 28, and with diabetes (P < 0.05).Conclusion: We report a significant linear positive correlation between weight-adjusted waist circumference index and metabolic disease-associated fatty liver disease, suggesting that weight-adjusted waist circumference index is a potential indicator for metabolic disease-associated fatty liver disease screening.Keywords: hepatic steatosis, hepatic fibrosis, abdominal obesity, weight-adjusted waist index, metabolic-associated fatty liver disease, cross-sectional study